Understanding radiation science basic nuclear and health physics - Shuler, James Mannie (Universal Publishers, 2006)
Information for students studying nuclear physics, health physics, and nuclear engineering on the basic principles of atomic structure, types of radiation, terminology and units, radiation biology, exposure and controls, background radiation, personnel monitoring, and radiation instrumentation.